Genetic association study of TNFAIP3, IFIH1, IRF5 polymorphisms with polymyositis/dermatomyositis in Chinese Han population. - Si Chen; Qian Wang; Ziyan Wu; Yuan Li; Ping Li; Fei Sun; Wenjie Zheng; Qingjun Wu; Chanyuan Wu; Chuiwen Deng; Fengchun Zhang; Yongzhe Li (PLoS ONE, 2014)
Single-nucleotide polymorphisms (SNPs) in the TNFAIP3, IFIH1, and IRF5 genes have been associated with several auto-inflammation diseases, while the susceptibility between these genes and idiopathic inflammatory myopathies (IIMs) were not reported. This study aimed to investigate whether TNFAIP3, IFIH1, and IRF5 gene polymorphisms confer susceptibility for the IIMs in Chinese Han population.A large case-control study of Chinese subjects with polymyositis (PM) (n = 298) and dermatomyositis (DM) (n = 530) was accomplished. 968 healthy and ethnically matched controls were available for comparison. Six SNPs in the TNFAIP3 region (rs2230926 and rs5029939), the IFIH1 gene (rs1990760 and rs3747517) and the IRF5 region (rs4728142 and rs729302) were assessed and genotyped using the Sequenom MassArray iPLEX platform.Our study indicated a strong allele association was observed in PM/DM and PM patients for rs2230926 (OR: 1.61, 95%CI: 1.20-2.16, P(c) = 7.5×10(-3); OR: 1.88, 95%CI: 1.30-2.74, P(c) = 4.0×10(-3), respectively) and rs5029939 (OR: 1.64, 95%CI: 1.21-2.21, P(c) = 6.0×10(-3); OR: 1.88, 95%CI: 1.28-2.76, P(c) = 5.5×10(-3), respectively). And rs2230926 and rs5029939 were significantly associated with interstitial lung disease (ILD) in PM/DM and PM patients (P(c) = 0.04 and P(c) = 0.016; P(c) = 0.02 and P(c) = 0.03, respectively). In addition, rs4728142 allele and genotype had significant association with PM/DM patients (P(c) = 0.026 and P(c) = 0.048, respectively). Further analysis with three logistic regression genetic models revealed statistically significant difference in the genotypic distribution in the PM/DM, PM or DM patients when the additive and dominant models were used.This was the first study to reveal TNFAIP3 and IRF5 polymorphisms were associated with PM/DM patients or these patients with ILD, indicating that TNFAIP3 and IRF5 might be the susceptibility gene for PM/DM patients in Chinese Han population.